2019
DOI: 10.3389/fpsyt.2019.00070
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Dyslipidemia and Lethality of Suicide Attempts: A Case-Control Study

Abstract: Evidence supports the existence of an association between dyslipidemia, psychiatric disorders, and suicide risk due to the effects of altered lipid profiles on serotoninergic neuron membranes. The aim of this study was to investigate the differences in c-reactive protein (CRP), thyroid functioning, total cholesterol, high lipoprotein density cholesterol (HDL-c), low-lipoprotein density cholesterol (LDL-c), and triglycerides (TG) serum levels in low lethality (LLSA) vs. high lethality suicide attempters (HLSA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 55 publications
(53 reference statements)
2
42
0
1
Order By: Relevance
“…Aguglia and co-workers [ 44 ] conducted a study with a sample of 632 attempts. They demonstrated that those who attempted high-lethality suicide had significantly lower total cholesterol.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Aguglia and co-workers [ 44 ] conducted a study with a sample of 632 attempts. They demonstrated that those who attempted high-lethality suicide had significantly lower total cholesterol.…”
Section: Resultsmentioning
confidence: 99%
“…Aguglia et al [ 44 ] showed that high lethality suicide attempters had considerably lower LDL compared to low lethality attempters and the control group [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have argued that lipid profiles, in particular, are linked to suicide attempts and their lethality in patients with severe mental disorders, including BD. However, evidence is still contrasting [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%